Peningkatan literasi dan manajemen keuangan rumah tangga melalui pelatihan dan pendampingan di Desa Sooko - Junior, Jonathan Hartono; Kristanto, Kenny Brian; Hadiputra, Vincentinus Felix; Linawati, Nanik (Penamas: Journal of Community Service, 2025)
This community service activity aims to enhance financial literacy and household financial management for the residents of Sooko Village. Based on initial observations, it was found that many families in the village struggle with financial management, including budget planning, debt management, and the wise use of financial services. The lack of understanding of basic financial concepts has led most of the community to fall into consumptive habits and fail to save for urgent needs. To address this issue, training, and mentoring were conducted using a service-learning approach, which combines academic learning with direct community interaction. The training program includes education on financial planning, distinguishing between needs and wants, and the practice of daily financial record-keeping. Additionally, individual coaching sessions and educational games were implemented to improve participants' understanding. The results of the activity showed that the community's awareness of the importance of financial management increased, with most participants beginning to adopt better financial practices. The success of this program confirms that an interactive educational approach can positively impact the financial well-being of the people of Sooko Village, Gresik.